The tonkin snub-nosed monkey Rhinopithecus avunculus population in the Quan Ba forest, north-east Vietnam: an identification of priority habitat for conservation - Dang, Nguyen Xuan; Nghia, Nguyen Xuan; The, Pham Van (Academia Journal of Biology, 2019)
The Tonkin Snub-nosed Monkey Rhinopithecus avunculus is among the World’s 25 most endangered primates. At present, the species is found only in few forest areas in Ha Giang and Tuyen Quang Provinces, north-east Vietnam with a total number not exceeding 250 individuals. The forest block in Cao Ma Po, Ta Van and Tung Vai Communes of Quan Ba District, Ha Giang Province (the Cao - Ta - Tung forest) harbors the second largest population of Tonkin Snub-nosed Monkey. This population was estimated to be conisted of about 30–35 individuals in 2007. However, it faces a number of serious threats (wildlife hunting, habitat degradation by widespread forest farming of Tsao-ko cardamom plant, etc.) that may lead the population to be extinct in near future. The population was reduced to 15–21 individuals in 2016 due to these threats. In 2017–2018, we conducted a study to identify a priority habitat area to establish the Quan Ba Tonkin Snub-nosed Monkey Conservation Area. The results of our study show that the distribution of the Quan Ba Tonkin Snub-nosed Monkey population is confined to a small area (about 5,000 ha) belonging to the Theng Chu Phin, Dao Dan Chai, Ta Lay mountains, the Hill 754 and a forest patch along the Vietnam-China border from the Post 283 to Post 295. This area harbors the best forest of the Cao - Ta - Tung area. The forest covers 92.3% of the area, and only 7.7% of the area is a non-forest land. There are two types of forest: evergreen broad-leaved forest (50.0% of total area) and limestone evergreen broad-leaved forest (42.3%). The evergreen broad-leaved forest has been degraded to medium and restoration status. Tsao-ko cardamom Amomum tsao-ko fields are widespread. The limestone evergreen broad-leaved forest of almost primary status remains in very steep slopes and limestone mountains. The Cao - Ta - Tung forest was designated as a watershed protection forest that allows farming of agricultural and medicinal plants inside the forest and the forest farming of Tsao-ko cardamom is widespread becoming the most serious threat to the long-term survival of the Tonkin Snub-nosed Monkey population. In order to ensure long-term survival of the Quan Ba Tonkin Snub-nosed Monkey population, the area of the Theng Chu Pin, Dao Dai Chai, Ta Lay, Tung Lau mountains, the Hill 754 and a forest patch along the Vietnam-China border from the Post 283 to Post 285 must be designated as a special-use forest, i.e. to establish a Quan Ba Tonkin Snub-nosed Monkey Conservation Area.